A Comparison of Physical Activity and Exercise Recommendations for Public Health: Inconsistent Activity Messages Are Being Conveyed to the General Public - Vincent J. Dalbo; Michael A. Carron (Sports)
We examined the similarities and differences between government-supported public health activity recommendations from the World Health Organization (WHO), the Centers for Disease Control and Prevention (CDC), the National Health Service (NHS), the Department of Health and Aged Care (DHAC), and one of the most renowned public health activity recommendations, the 10,000 Steps Program. The findings derived from our evaluation suggest a lack of consistency in public health activity recommendations, including the nomenclature used to describe aerobic activity, the amount of time required per week to meet the minimum recommendation for moderate and vigorous activity, and variations in the intensities required to meet aerobic activity recommendations. We also found that moderate-intensity activity (3.0 to less than 6.0 METS) is achieved across the lifespan with normal (i.e., mean), rather than vigorous, walking speeds; this suggests the MET level for moderate-intensity activity may need to be re-examined. The suggested strength activities must also be considered to ensure that the activities maintain or improve strength in the general public. Among the reviewed recommendations, none distinguished between physical activity and exercise, which may contribute to the low levels of exercise participation among the general public. Since exercise is medicine, the most recognized government-supported public health activity recommendations should place a greater emphasis on exercise over physical activity. Moreover, given the low levels of activity in the general public, more care should be given to provide a consistent, clear, and direct message regarding activity recommendations.